Ownership of knowledge: the role of patents in pharmaceutical R&D - Carlos María Correa (The World Health Organization, 2004)
Both the public and the private sectors contribute to research and development (R&D) in pharmaceuticals. The public sector originates many of the discoveries of new drugs. The private sector, which focuses on development, is heavily reliant on patents. Though patents are presumed to reward genuine inventions, lax rules on patentability and shortcomings in procedures permit protection to be obtained on a myriad of minor developments. These patents, though weak and possibly invalid in many cases, are used to restrain competition and delay the entry of generic competition. Developing countries should design and implement their patent laws so as to prevent strategic patenting and promote competition and access to medicines.